GENEZA I PROFIL CZECHOSŁOWACKIEGO PRAWA WYZNANIOWEGO I REPUBLIKI W LATACH 1918-1938 - Leszczyński, Paweł A. (Zeszyty Prawnicze, 2016)
GENESIS AND PROFILE OF CZECHOSLOVAK ECCLESIASTICAL LAW TURING THE PERIOD OF 1ST REPUBLIC 1918-1938 Summary The aim of this article is to describe original model Church – State relationships in interwar Czechoslovakia. It was democratic and secular state. During of this period Czechoslovak ecclesiastical law was mixed composition of two factors: partially austrohungarian and modern and modern and liberal conception of human and civil rights. Legal documents First Czechoslovak Republic considered the guarantee values of modern constitutionalism as: freedom, equality before the law, rule of law, justice, protection of national minorities rights. Legal status of denominational communities since beginning this state to collapse in 1938 (after illegal Munich Agreement, which was signed by Hitler, Mussolini, Daladier and Chamberlain) was considered. The article describe also historical heritage of confessional relations, the relation of political forces and persons (for example first President T.G. Masaryk) to religion and churches in this period, legal ground of freedom of conscience and religion and opportunities for teaching religion at public schools.